2015
DOI: 10.1109/ted.2014.2386338
|View full text |Cite
|
Sign up to set email alerts
|

Vane-Loaded Planar Helix Slow-Wave Structure for Application in Broadband Traveling-Wave Tubes

Abstract: Dispersion control of a planar helix slow-wave structure (SWS) using vane loading for applications in travelingwave tubes has been studied. The addition of metal vanes and coplanar ground planes to the planar helix structure has been investigated with the help of simulations aimed at achieving low or negative dispersion. It is shown that, similar to the case of circular helix, the addition of metallic vanes to the planar helix can produce a flatter dispersion curve or negative dispersion characteristics. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Fig. 14 presents a typical result obtained from the PIC simulations using CST Particle Studio [26]. Fig.…”
Section: Power Output Of the Overall Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 14 presents a typical result obtained from the PIC simulations using CST Particle Studio [26]. Fig.…”
Section: Power Output Of the Overall Assemblymentioning
confidence: 99%
“…The dispersion curve is different from a normal helical SWS in which phase velocity falls with increasing frequency. Such a behaviour (including negative dispersion) is seen when the metal shield comes rather close to the SWS and there are also CPW ground planes[26]. The coupling impedance shown in Fig.3(b) has a relatively high value of about 23.6 Ohms at 100 GHz.…”
mentioning
confidence: 92%
“…Other than metal vanes, coplanar ground planes in PH-SEC also have significant effect on dispersion. The simulation and measurement studies show that stronger dispersion control can be achieved from a PH-SEC by using metal vanes together with extended coplanar ground planes [74]. The studies on dispersion control lead to the development of microfabricationcompatible PH-SEC SWS shown in Fig.…”
Section: Dispersion Controlmentioning
confidence: 94%
“…Three types of metal wanes namely T-shaped, solid, and thin vanes have been found very effective for circular helix. The impact of such metal vanes on the characteristics of fundamental space harmonics in PH-SEC has been studied [74]. The studies show that, similar to the case of circular helix, a flatter dispersion curve or negative dispersion characteristics can be obtained from PH-SEC using metal vanes.…”
Section: Dispersion Controlmentioning
confidence: 99%
“…As for high speed Ka-band communication, a small diameter (< 1mm) of Slow-Wave Structure (SWS) is needed [12], thus driving increased demands for miniaturized TWTAs. Besides, in a study reported by our research group, a Planar Helix-SWS (PH-SWS) has been proposed to be fabricated by using silicon-based microfabrication techniques [13]. Furthermore, in the attempt to incorporate sheet beam into the PH-SWS TWTA, the design of a sheet-beam electron gun is generated [14].…”
Section: Chapter 1: Introduction and Overviewmentioning
confidence: 99%